Activating MoS2 Basal Plane via Non‐noble Metal Doping For Enhanced Hydrogen Production. Issue 5 (1st February 2023) - Xie, Zhongqi; Wu, Yue; Zhao, Ya; Wei, Mengyuan; Jiang, Qing‐Song; Yang, Xiao; Xun, Wei
Abstract: MoS2 is a promising electrocatalyst for hydrogen evolution reaction (HER). However, it is not conducive to the adsorption and dissociation of water, due to the inert basal plane. Herein, we determined a series of non‐noble metal doped MoS2 materials with high catalytic activity through first‐principles calculation. Under standard conditions, we found through Pourbaix diagram that the basal plane of the doped material would not be terminated by OH* or O*, and could maintain high stability in acidic or alkaline solutions. The formation of new electronic states in the doped material near the Fermi level and subsequent bonding with H atoms is energetically favorable, which activates the inert basal plane. With the increase of doping concentration, ΔG H will further approach 0 eV and produce a large exchange current density. We found that the ΔG H increases monotonically with the increase of the lowest occupied state E of the doped material, indicating the physical origin of the excellent hydrogen evolution activity caused by doping. Abstract : The binding energy between the MoS2 base plane and the H atom is increased by doping with non‐noble metal elements, and new electronic states appear near the Fermi level. The subsequent bonding with the H atom is energetically favorable, which activates the catalytic activity of the base plane. With the increase of doping concentration, ΔGH will further approach 0 eV and produce a larger exchange current density.